Synthesising amorphous Cr–Mo alloy via mechanical alloying of immiscible Cr and Mo elements. (April 2015) - Sun, C. F.; Xi, S. Q.; Zhang, Y.; Zheng, X. X.; Zhou, Y.; Zhou, J. E.
Abstract : In the present study, the amorphous Cr–Mo alloy was synthesised by mechanical alloying of immiscible Cr and Mo elements (Cr-35at.%Mo powders) at a temperature of ∼260 K under Ar atmosphere. The X-ray diffraction and transmission electron microscopy analysis showed that there was a transition between the Cr(Mo) solid solution and amorphous Cr–Mo phase during mechanical alloying. With increasing milling time, the initially formed Cr(Mo) solid solution transformed to the amorphous Cr–Mo alloy, which then transformed to Cr(Mo) solid solution once more. The underlying reason for this transition is likely the metastable nature of these two phase, i.e., solid solution and amorphous alloy.